Group Investigasi (GI): Model Pembelajaran Kooperatif untuk Peningkatan Hasil Belajar Siswa - Rosanti Rosanti; Purwati Yuni Rahayu (Faculty of training and education, Pamulang university, 2022)
ABSTRACTThis study aims to prove a significant difference in the learning outcomes of class XI IPS before and before students use the group investigation cooperative learning model at MA Al-Muhtadi. This study uses a quantitative approach with a quasi-experimental research method and the design used is One group pretest-posttest design. This study uses a quantitative approach, in this case students act as research objects. In this study data collection using pretest and posttest. The results of this study are, the results of studying Economics before using the group investigation type cooperative learning model obtained an average pretest of 52.30 while after using the group investigation type of cooperative learning model the posttest average was 73.30. Based on the average posttest results, learning using the group investigation type cooperative learning model has better learning outcomes. Based on the t-test Paired Sample T Test, in this study, the output of the Paired Sample Test was obtained with a value of sig 0.00 <0.05, which means Ha was accepted, so it can be said that there is a significant effect of the group investigation type cooperative learning model on student learning outcomes in the eyes economics class XI IPS at MA Al-Muhtadi.Keywords: Cooperative Model; Group Investigations; Learning outcomes